Burden of enterotoxigenic Escherichia coli and shigella non-fatal diarrhoeal infections in 79 low-income and lower middle-income countries: a modelling analysis. Issue 3 (March 2019) - Anderson, John D; Bagamian, Karoun H; Muhib, Farzana; Amaya, Mirna P; Laytner, Lindsey A; Wierzba, Thomas; Rheingans, Richard
Summary: Background: Enterotoxigenic Escherichia coli (ETEC) and shigella are two major pathogens that cause moderate-to-severe diarrhoea in children younger than 5 years. Diarrhoea is associated with an increased risk of stunting, which puts children at risk of death due to other infectious diseases. Methods: We modelled ETEC-related and shigella-related mortality and the effect of moderate-to-severe diarrhoea episodes to determine the number of children with stunting due to these infections in 79 low-income and lower middle-income countries. We applied population attributable risk for increased number of deaths due to other infectious diseases in children who are stunted. We calculated 95% uncertainty intervals (UIs) for the point estimates. Findings: In children younger than 5 years, we estimate 196 million (95% UI 135–269) episodes of ETEC and shigella diarrhoea occur annually, resulting in 3·5 million (0·8–5·4) cases of moderate-to-severe stunting and 44 400 (29 400–59 800) total ETEC deaths and 63 100 (44 000–81 900) total shigella deaths in 2015. Additional infectious disease mortality due to stunting resulted in increases of 24% (8–34; for ETEC) and 28% (10–39; for shigella) over direct deaths due to diarrhoeal episodes. The distribution of mortality and morbidity varied geographically, with African Region and Eastern Mediterranean Region countries bearing the greatest burden. Interpretation: The expanded effects of non-fatal ETEC and shigella-related diarrhoeal episodes can have lasting consequences. Prevention of these infections could reduce the risk of direct death and stunting and deaths due to other infectious diseases. Understanding the countries and populations with the highest disease risk helps to target interventions for the most vulnerable populations. Funding: The Bill & Melinda Gates Foundation.